Top 10 evidence-based recommendations from the Brazilian Society of Infectious Diseases for the Choosing Wisely Project - Pasqualotto,Alessandro C. (2019)
ABSTRACT The Choosing Wisely Initiative aims to collect statements from medical societies all over the world on medical interventions that result in no benefit to patients, with the potential to cause harm. In this article we present the views of the Diagnostic Laboratory Group at the Brazilian Society of Infectious Diseases (SBI). Ten experts from SBI were asked to list 10 diagnostic tests that were perceived as unnecessary in the field of infectious diseases. After voting for the more relevant topics, a questionnaire was sent to all SBI members, in order to select for the most important items. A total of 482 votes were obtained, and the top 10 results are shown in this manuscript. The Choosing Wisely statements of SBI should facilitate clinical practice by optimizing the use of diagnostic resources in the field of infectious diseases.